2017
DOI: 10.1111/ppl.12563
|View full text |Cite
|
Sign up to set email alerts
|

Sterol glycosyltransferases required for adaptation of Withania somnifera at high temperature

Abstract: Heat is a major environmental stress factor that confines growth, productivity, and metabolism of plants. Plants respond to such unfavorable conditions through changes in their physiological, biochemical and developmental processes. Withania somnifera, an important medicinal plant, grows in hot and dry conditions, however, molecular mechanisms related to such adaptive properties are not known. Here, we elucidated that members of the sterol glycosyltransferases (SGT) gene family play important roles in the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Comparison of lipid composition of a heat-tolerant sorghum cultivar and a heat-susceptible sorghum cultivar identified differences in levels of SGs and ASGs under heat stress, with the heat-tolerant cultivar displaying higher levels of sterol derivatives, consistent with the notion that SGs and ASGs might play a role in improving plant response to heat [ 8 ]. Singh et al [ 47 ] showed that silencing of the genes for three glycosyltransferases that form sterol glycosides in the medicinal plant, Withania somnifera , reduced the photosynthetic rate and increased the transpiration rate of the plants under heat stress. Furthermore, ugt80B1 mutants of Arabidopsis, in which SG content is reduced by 65–80%, exhibited decreased survival of seedlings grown on nutrient agar medium for 5 days at 42 °C [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of lipid composition of a heat-tolerant sorghum cultivar and a heat-susceptible sorghum cultivar identified differences in levels of SGs and ASGs under heat stress, with the heat-tolerant cultivar displaying higher levels of sterol derivatives, consistent with the notion that SGs and ASGs might play a role in improving plant response to heat [ 8 ]. Singh et al [ 47 ] showed that silencing of the genes for three glycosyltransferases that form sterol glycosides in the medicinal plant, Withania somnifera , reduced the photosynthetic rate and increased the transpiration rate of the plants under heat stress. Furthermore, ugt80B1 mutants of Arabidopsis, in which SG content is reduced by 65–80%, exhibited decreased survival of seedlings grown on nutrient agar medium for 5 days at 42 °C [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our group tried repeatedly to test the hypothesis that SGs and ASGs play a role in growth or survival of Arabidopsis under heat stress. In our experimental design, 30-day-old double mutants of UGT80A2 and UGT80B1 [ 47 ] and wild-type plants were subjected to severe heat stress, 45 °C for 12 h, or a control treatment (21 °C). This 45 °C treatment was three times longer than for Path 3 in the experiment described in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The key feature of proline by which it quenches singlet oxygen in somatic cells is the secondary amine structure of pyrrolidine [ 54 ]. In our previous study, we showed that the exposure of boar sperm to DL-pipecolinic acid shared secondary amine with proline improved sperm progressive motility; however, the THFA failed to do so, because lacks a secondary amine.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the profile of glycosylated sterols have been widely related with the plant response to different abiotic stresses (Palta et al, 1993; Mishra et al, 2013; Pandey et al, 2014; Mishra et al, 2015; Saema et al, 2016; Takahashi et al, 2016; Singh et al, 2017). However, there are less experimental evidence supporting their involvement in biotic stress responses (Pandey et al, 2014; Singh et al, 2016; Mishra et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Forward- and reverse-genetic approaches have also shown that changes in SGT expression levels are associated to altered responses of different plant species to abiotic stress conditions. An increased sensitivity to heat and cold stress has been reported in Arabidopsis and W. somnifera plants with reduced levels of SGT (Mishra et al, 2015; Singh et al, 2017), whereas enhanced tolerance to heat, cold, and salt stress has been associated to overexpression of SGT in Arabidopsis , tobacco, and W. somnifera , respectively (Mishra et al, 2013; Pandey et al, 2014; Saema et al, 2016). These observations are consistent with the induction of SGT genes in response to abiotic stress reported in tomato (Ramírez-Estrada et al, 2017), W. somnifera (Chaturvedi et al, 2012), and cotton (Li et al, 2014), and also with changes observed in the relative proportions of glycosylated sterols in the plasma membrane of oat, rye, and potato in association with cold acclimation and freezing tolerance (Palta et al, 1993; Takahashi et al, 2016), during tomato and apple fruit chilling and after tomato fruit rewarming (Whitaker, 1991; Whitaker, 1994; Rudell et al, 2011), in wheat leaves under high day and night temperature (Narayanan et al, 2016), and in Arabidopsis under drought stress conditions (Tarazona et al, 2015).…”
Section: Introductionmentioning
confidence: 99%